Profiling of Humoral Immune Response in Typhoid Patients against Differentially Extracted Whole Cell Bacterial Protein Derived from S. typhi and S. spp - Abdul Lateef Khan, Khairunnisa; Sheik Abdul Kader, Zainoodin (Interdisciplinary Perspectives on Infectious Diseases, 2023)
Typhoid fever is a multiorgan infectious disease caused by Salmonella typhi. It is transmitted through fecal oral route and can be fatal without proper treatment. Therefore, early diagnosis of typhoid fever is crucial. In the previous study, we have developed TYPHOIDYNE EIA, which showed excellent synergy between the genus conserved and species-specific antigens in the serodiagnosis of typhoid fever. TYPHOIDYNE EIA can effectively detect and differentiate typhoid patients, typhoid vaccinated subjects, healthy subjects, and subjects with other febrile illnesses. Following the successful development of TYPHOIDYNE EIA, in this report, we further characterize the antigenic components of differentially extracted S. typhi and S. spp recognized by IgM, IgG, and IgA antibody isotypes in typhoid patients and possible typhoid carrier by the western blot (WB) assay. The WB characterization revealed a dynamic pattern of recognition, with significant variations in the number of antigenic bands observed between the differentially extracted arrays of antigens. The reactivity of patient’s sera was divided into 3 regions, with region 1 (≥55 kDa) showing the strongest reactivity followed by region 2 (54 kDa–34 kDa) and region 3 (<34 kDa). Overall, the good synergy expressed in these bands suggests the potential role of these proteins in differentiating typhoid patients with possible typhoid carrier. The antigenic bands highlighted in this study are also identified as prospective biomarkers for diagnostic use and vaccine development.